EVALUASI KINERJA LALU LINTAS SEBELUM DAN SESUDAH ADANYA FLYOVER GANEFO MRANGGEN (DEMAK) - Khoirunnisa, Novia (Jurnal Teknik Indonesia, 2022)
The flyover construction is an effort to break down traffic jams in Indonesia. One of them is the construction of the Ganefo Mranggen (Demak) flyover. The work on the construction of this flyover has been initiated by the Bina Marga Office of Central Java Province since 2015. When this research took place in 2021, the flyover was still in the process of being completed. So the purpose of this paper is to know the degree of saturation when the flyover is functioning. In this study using research methods in the form of data collection. Because this research is an investigative activity to obtain facts from known symptoms, seek factual information, collect data for evaluation. In this study, secondary data from the Office of Highways 2019 was used. Data collection was obtained from literature studies and direct surveys. Secondary data is data obtained directly from the Related Office. This data is in the form of traffic volume survey data and road geometry. The result of this research is that after construction of the flyover the degree of saturation is reduced which was originally for the direction of Semarang - Purwodadi of 0.45 with a service level of C to 0.17 with a service level of A. As for the opposite direction or the direction of Purwodadi - Semarang, the degree the initial saturation was 0.81 with service level D to 0.33 with service level B. So it can be seen that the flyover construction has a significant impact on the service level of road performance.Keywords: flyover, degree saturation, point of conflict